'My independent streak may get in the way': how older adults respond to falls prevention education in hospital. Issue 7 (26th July 2016) - Hill, Anne-Marie; Francis-Coad, Jacqueline; Haines, Terry P; Waldron, Nicholas; Etherton-Beer, Christopher; Flicker, Leon; Ingram, Katharine; McPhail, Steven M
Abstract : Objectives: The aim of the study was to determine how providing individualised falls prevention education facilitated behaviour change from the perspective of older hospital patients on rehabilitation wards and what barriers they identified to engaging in preventive strategies. Design: A prospective qualitative survey. Methods: Older patients (n=757) who were eligible (mini-mental state examination score>23/30) received falls prevention education while admitted to eight rehabilitation hospital wards in Western Australia. Subsequently, 610 participants were surveyed using a semistructured questionnaire to gain their response to the in-hospital education and their identified barriers to engaging in falls prevention strategies. Deductive content analysis was used to map responses against conceptual frameworks of health behaviour change and risk taking. Results: Participants who responded (n=473) stated that the education raised their awareness, knowledge and confidence to actively engage in falls prevention strategies, such as asking for assistance prior to mobilising. Participants' thoughts and feelings about their recovery were the main barriers they identified to engaging in safe strategies, including feeling overconfident or desiring to be independent and thinking that staff would be delayed in providing assistance. The most common task identified as potentially leading to risk-taking behaviour was needing to use the toilet. Conclusions: Individualised education assists older hospital rehabilitation patients with good levels of cognition to engage in suitable falls prevention strategies while on the ward. Staff should engage with patients to understand their perceptions about their recovery and support patients to take an active role in planning their rehabilitation.